Efektivitas 3 spesies lebah madu sebagai agen polinasi untuk meningkatkan produktivitas (>40%) biji jarak pagar (Jatropha curcas) pada ekosistem iklim basah - . Kasno; A.E. Zainal Hasan; Dedi Sholeh Efendi; . Syaefuddin (Jurnal Ilmu Pertanian Indonesia, 2010)
The physic nut (Jatropha curcas) is one of potential plant for producing biodiesel, however efforts to socialization have still encounter constraints. The production system so far has not come to a level of attractive to the fellow farmers due to low productivity. Therefore further researches on production system are still urgently needed. This research entitled "The effectiveness of Three Species of Honey Bees as Pollinating Agent to Increase Seed Productivity" was carried out at Pakuwon, Sukabumi. The study site is a physic nut's seeds production center. The immediate objectives of the research was to identify the indirect impact of pollination of honey bees on physic nut farm on increasing its seed productivity while the further objective was to increase former's income. To achieve the immediate objective of the research, a set of experiment was conducted. Three species of honey bees namely Apis mellifera, Apis cerana and Trigona iridipenis were tested as pollinating agent to flowering physic nut plants under screen coverage. The size screen cover was 8 m long, 4 m wide and 2.5 m to cover 32 flowering physic nut plants. The treatment consisted of one and two colonies of honey bee species were released into each screened plot for 3 weeks. The untreated plot has no bee colony. The treatment was replicated 3 times. Complete Randomized Design procedure was followed in the experiment. Fruit sampling was done 50-55 days after colonies placement. Results of the first year experiment shows that honey bees as pollinating agent, especially A . cerana and A. mellifera provide significant positive indirect impact on seed productivity of physic nut plants. Assuming the market price of seed is not decreasing, such increase of seed productivity may also increase farmer's income from selling the harvested seeds.